The Analysis of Reading Strategies Used by Teachers in Teaching Reading Comprehesion at MAN 4 Pesisir Selatan - Efendi, Agfa; Rani, Yati Aisya (Journal of English Language Teaching, 2024)
The purpose of this study is: (1) To find out the implementation of beginning reading of reading strategies used by teachers in teaching reading comprehension at MAN 4 Pesisir Selatan. (2) to find out the implementation of during reading of reading strategies used by teachers in teaching reading comprehension at MAN 4 Pesisir Selatan. (3) to find out the implementation of after reading of reading strategies used by teachers in teaching reading comprehension at MAN 4 Pesisir Selatan. This research used descriptive research. The sample of this study were English teachers. Observations checklist and interview guidelines were used to collect data. In the reading strategies, there are three steps in applying reading strategies, they are: beginning reading step, during reading step, and after reading step. The analysis of reading strategies in this school was not implemented well. It still needs improvement. The problems found are the teacher's lack of knowledge regarding reading strategies themselves, the teacher's lack of approach to students, which causes the teacher's relationship with students to not be established well, and the application of time in which learning is ineffective.